Impact of landscape patterns on ecological vulnerability and ecosystem service values: An empirical analysis of Yancheng Nature Reserve in China. (January 2017) - Zang, Zheng; Zou, Xinqing; Zuo, Ping; Song, Qiaochu; Wang, Chenglong; Wang, Junjie
Highlights: An ecological vulnerability assessment indicator system was constructed for coastal wetland. Fluctuation index of ecosystem services was calculated based on improved model. Remote sensing data were employed to analyze the landscape pattern index of the study area. The relationships among landscape patterns, ecological vulnerability and ecosystem services were analyzed. Abstract: In this study, an ecological vulnerability assessment indicator system was constructed using the "exposure–climate sensitivity–adaptive capacity" framework according to the theory of ecological vulnerability. An improved ecosystem service value calculation model was proposed based on empirical parameters. Using Yancheng Nature Reserve in China as an example, we employed remote sensing data to conduct an empirical analysis of the changes in the spatiotemporal pattern, ecological vulnerability, and ecosystem services of typical landscape types over the period from 1987 to 2013. The statistical results derived from landscape pattern indices (LPIs) showed that during the investigation period, three natural wetland landscape types (i.e., Spartina alterniflora, Suaeda glauca, and Phragmites australis ) showed gradually increased fragmentation in the study area. The ecological vulnerability scores of the major landscape types (in descending order) were P. australis (0.053), farmland (0.047), S. alterniflora (0.042), S. glauca (0.031), and bare mud flat (0.002). The results derived from the ecosystem service value fluctuation index ( ESVFI ) showed that from 1987 to 1997, the value of the ecosystem services provided by S. glauca and P. australis wetlands decreased, whereas that of S. alterniflora wetlands increased continuously. From 2002 to 2013, the value of the ecosystem services provided by all three types of natural wetland showed a downward trend. In conclusion, the combined effects of human and natural factors, including the expansion of farmland and the invasion of S. alterniflora, and changes in seawater erosion and deposition led to changes in the landscape patterns, ecological vulnerability, and ecosystem services of the Yancheng Nature Reserve during the investigation period. The results indicate that a "dual adaptive" management system based on natural succession and supplemented by appropriate manual intervention should be implemented, and the management efficiency and flexibility should be improved to meet the common needs of biodiversity conservation and economic development.